DEVIASI FONOLOGIS TUTURAN BAHASA INDONESIA ANAK - Yulianto, Bambang (Diksi, 2007)
This article explains the phonological deviations in Indonesian utterancesof children with the age range from 1.0 to 2.6, which represents a stage of languagedevelopment with the children of the age range from 1.0 to 1.6 producing their firstsingle-word utterances (SWU), those of the age range from 1.6 to 2.0 producingtheir first word combinations (FWC), and those of the age range from 2.0 to 2.6producing their first simple and complex sentences (SCS). The data show that 11phonological deviation patterns are found in SWU, 13 phonological deviationpatterns are found in FWC, and 7 phonological deviation patterns are found inSCS. On the basis of these available patterns, it could be stated that (1) the mostproductive patterns are stopping, gliding, nasalizing, and cluster reduction, (2) thedeviation patterns tend to decrease as age increases, (3) as children get older, thereduplication pattern is abandoned and the deletion pattern decreases, and (4) alateralization pattern occurs when children begin producing SCS. Most of thepatterns are universal since they also occur in the utterances of subjects of otherresearchers.Keywords : patterns of phonological deviations, children utterances, underlyingrepresentation, phonetic representation, SWU, FWC, SCS